Design of a Cylindrical Compliant Linear Guide with Decoupling Parallelogram Mechanisms - Tinghao Liu; Guangbo Hao (Micromachines, 2022)
A conventional linear guiding mechanism refers to the slide rail guides composed of multiple assemble parts. These guiding mechanisms suffer from many adverse effects, including lubrication, wear and assembly issues. A novel compliant guiding mechanism is proposed in this paper to address these common problems, and this mechanism transfers or transforms motion, force and energy via the deformation of flexible members. This linear guide is designed in a cylindrical shape, and the centre platform moves along its axis (i.e., the motion direction). The proposed linear guide consists of several in-parallel curved compound double parallelogram mechanisms (CDPMs) connected by the same number of decoupling parallelogram mechanisms. Nonlinear finite element analysis (FEA) is used for stiffness analysis and shows that applying the decoupling mechanisms to the detached linear guide (the in-parallel curved CDPMs only) can dramatically improve the stiffness in undesired movement (bearing) directions while keeping its original stiffness along its axis. The nonlinear FEA can capture the stiffness variation by considering all the structural deformation. The issue of bearing-direction stiffness degradation of the detached linear guide is dealt with by applying decoupling mechanisms. The static experimental test is conducted on a 3D printed prototype and shows that the stiffness in the motion direction is nearly constant (linear). The results obtained from the experimental test show good agreement with those obtained from the nonlinear FEA with a maximum error of 9.76%.